ANALISIS KESALAHAN PENULISAN SANDHANGAN DALAM PEMBELAJARAN AKSARA JAWA KELAS IV SDN 2 GEBANG - Fandy Ahmad Prasetyo (FKIP Unirow Tuban, 2019)
The fourth grade students of SDN 2 Gebang experienced a problem which was the low level of students' ability to write sandhangan. This type of research is qualitative research using descriptive analytical methods with a case study approach. Data collection techniques in this study are: tests, interviews, and documentation. The results showed errors in grade IV SDN 2 Gebang in writing Pengkal as many as 20 errors, Keret as many as 18 errors, Chakra as many as 16 errors, Screen 13 as many errors, Wignyan 12 as many errors, Wulu as many as 12 errors, Geckos as many as 11 errors, Taling as many as 11 errors, Tribe 10 errors, Pepet as many as 10 mistakes, Taling fight as many as 9 mistakes, and Pangkon as many as 5 mistakes. The factors that caused students to write mistakes were: the students had not memorized the form of support, students were unable to apply the rules of writing the students and the students had not memorized the function of the writing. Based on the results of the study, it can be concluded that the learning to write sandhangan in SDN 2 Gebang has not run optimally. Almost all students make mistakes in writing the handbook. Most writing errors occur in the scaling constraints and the least errors occur in the Pangkon Sandhangan.